Features And Methodology of Creative Tasks (European Journal of Pedagogical Initiatives and Educational Practices, 2023)
The article explores the concept of creative tasks, psychological and pedagogical approaches to their development, interdisciplinary integration, assessment criteria, and their role in fostering students' independent and innovative thinking skills.